2020
DOI: 10.3389/fpls.2019.01814
|View full text |Cite
|
Sign up to set email alerts
|

Untangling the Evolution of American Wild Grapes: Admixed Species and How to Find Them

Abstract: Natural hybridization and introgression are central evolutionary processes in grape genus (Vitis). On the other hand, the interspecific relationships among grapes, the directionality of the inferred admixture events and the parents of hybrids are not yet completely clarified. The grapes are economically important crops characterized by tendrils used to climb on the trees and the fruits harvested by humans especially for the consumption or to produce wines and liquors. The American grapes (ca. 30 species) are r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 82 publications
6
35
0
Order By: Relevance
“…As Treemix requires genotypes to be called, PCAngsd was used to call genotypes from the GLs with a 95% posterior probability cutoff using estimated inbreeding coefficients as a prior. When looking at the distribution of fraction of missing genotypes per site, we observed a peak at 10%, and decided to exclude any sites with greater than 20% missing data across samples, consistent with cutoffs in other studies ( Brandenburg et al 2017 ; Zecca et al 2019 ). We also excluded sites for which data are completely missing within any one cluster as required by Treemix, leaving 29,145 SNPs for analysis.…”
Section: Methodsmentioning
confidence: 59%
“…As Treemix requires genotypes to be called, PCAngsd was used to call genotypes from the GLs with a 95% posterior probability cutoff using estimated inbreeding coefficients as a prior. When looking at the distribution of fraction of missing genotypes per site, we observed a peak at 10%, and decided to exclude any sites with greater than 20% missing data across samples, consistent with cutoffs in other studies ( Brandenburg et al 2017 ; Zecca et al 2019 ). We also excluded sites for which data are completely missing within any one cluster as required by Treemix, leaving 29,145 SNPs for analysis.…”
Section: Methodsmentioning
confidence: 59%
“…Hybridisation is a natural process generally attributed to taxa range changes but in certain circumstances can be imputed to human activity. In recent years, molecular studies have proved that interspecific hybridisation and introgression are central processes in the evolution of Vitis genus [ 79 , 82 , 102 , 103 ]. Introgression is considered a process mediated by the transfer of genes through repeated backcrosses and when occurring from crops to its wild relatives can have deleterious consequences on the genetic structure and conservation of populations [ 104 ].…”
Section: Introgression Between Wild and Domesticated Grapevinementioning
confidence: 99%
“…The result of the present study is in line with [ 13 , 14 ], that clearly and concisely reported that wild grapevines were vigorous compared to the modern grapes. This might be mainly due to genetic differences among the grapevine cultivars [ 15 ], sunlight distribution [ 9 ], and poor canopy management [ 16 ].…”
Section: Resultsmentioning
confidence: 99%